A new species of Arachnanthus from the Red Sea (Cnidaria, Ceriantharia) - Stampar, Sérgio N. [UNESP]; El Didi, Suraia O. [UNESP]; Paulay, Gustav; Berumen, Michael L. (My University, 2018)
A new species of the genus Arachnanthus (Cnidaria: Ceriantharia), Arachnanthus lilith Stampar & El Didi, sp. n., is described. This species is widely distributed in the Red Sea, and recorded from 2–30 m depths. Arachnanthus lilith Stampar & El Didi, sp. n. is the fifth species of the genus and the first recorded from the Red Sea. The number of labial tentacle pseudocycles, arrangement of mesenteries, and distribution of acontioids allow the differentiation of the new species from other species of the genus.
Keywords: Anthozoa; Biodiversity; Coral reefs; Indo-West pacific; Marine invertebrates; Taxonomy